2017
DOI: 10.1002/eat.22778
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–behavioral therapy for eating disorders in primary care settings: Does it work, and does a greater dose make it more effective?

Abstract: The level of effectiveness shown here is comparable to that previously demonstrated by more specialist services in secondary and tertiary care. The nonlinear association between number of sessions and recovery highlights the importance of early change, across the eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 20 publications
4
28
0
Order By: Relevance
“…Women who did not receive outpatient treatment following their inpatient treatment did not fare worse than women who received treatment. These findings are in line with results from two previous studies (Bell et al, 2017;Rose & Waller, 2017), indicating that a meaningful change in symptoms is unlikely to occur after the initial treatment phase and rapid response may be far more crucial for favorable long-term outcomes than high treatment doses. In line with previous findings, in our sample abstinence from binge eating and compensatory behaviors at hospital discharge predicted abstinence 18 months later (Jacobi et al, 2017), while treatment dose did not have any effect.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Women who did not receive outpatient treatment following their inpatient treatment did not fare worse than women who received treatment. These findings are in line with results from two previous studies (Bell et al, 2017;Rose & Waller, 2017), indicating that a meaningful change in symptoms is unlikely to occur after the initial treatment phase and rapid response may be far more crucial for favorable long-term outcomes than high treatment doses. In line with previous findings, in our sample abstinence from binge eating and compensatory behaviors at hospital discharge predicted abstinence 18 months later (Jacobi et al, 2017), while treatment dose did not have any effect.…”
Section: Discussionsupporting
confidence: 91%
“…In one study, 47 patients with eating disorders received between 7 and 33 sessions of outpatient treatment and the number of treatment sessions and the level of improvement was unrelated past the eighth to twelfth session; the dose-response-relationship was nonlinear (Rose & Waller, 2017). In one study, 47 patients with eating disorders received between 7 and 33 sessions of outpatient treatment and the number of treatment sessions and the level of improvement was unrelated past the eighth to twelfth session; the dose-response-relationship was nonlinear (Rose & Waller, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, improvements for most variables were observed at mid-treatment, and posttreatment results were largely maintained at both follow-up points. Abstinence, remission, and good outcome rates were comparable to the initial pilot study and to efficacy and effectiveness studies of CBT-ED and CBT-GSH using both experienced and inexperienced therapists (Banasiak, Paxton, & Hay, 2005;Byrne et al, 2011;Cachelin et al, 2014;Carter & Fairburn, 1998;Fairburn et al, 2009Fairburn et al, , 2015Knott et al, 2015;Rose & Waller, 2017;Signorini et al, 2018;Turner et al, 2015; EDE-Q, Eating disorder examination questionnaire; CIA, clinical impairment assessment; BMI, body mass index; DASS21, depression anxiety and stress scales; ED, eating disorder; OR, odds ratio. Objective bingeing and purging were also analysed using behavioural items from the EDE-Q (where behaviours are assessed over a 4-week period).…”
Section: Discussionmentioning
confidence: 55%
“…Evidence suggests that under specialist supervision, novice therapists are able to deliver outcomes comparable with experienced therapists in clinical trials for mental health issues, including eating disorders (e.g., Öst, Karlstedt, & Widén, ; Zandberg & Wilson, ). Several studies of guided self‐help (CBTgsh) for binge eating found comparable results with experienced therapists with a variety of novice or nonspecialist therapists (see Wilson & Zandberg, , for a review) and effectiveness studies of CBT‐ED with a combination of experienced and nonexperienced therapists also demonstrate comparable outcomes (Rose & Waller, ; Turner et al, ; Wade, Byrne, & Allen, ). Given the phenomenon of therapist drift away from evidence‐based practice over time (Cowdrey & Waller, ; Waller & Turner, ), associated with decreasing effectiveness over time (Goldberg et al, ), the use of trainee psychologists under expert supervision is both viable and cost‐effective.…”
Section: Introductionmentioning
confidence: 97%